Normally, this is a difficult form of the equation to deal with. To change it into a more familiar form, we can do this:
4x + 3y = 0
3y = -4x
y = (-4/3)x
-2x plus 3y equals 1
7
-2x+3y=1 3y=1+2x y=(1+2x)/3 Then proceed to find points by plugging in given or arbitrary values of x.
2x-11
2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41
-2x plus 3y equals 1
7
3x + y = c where c is any constant number of your choice.
(2,7)
5x+3y
4.34684352143
-2x+3y=1 3y=1+2x y=(1+2x)/3 Then proceed to find points by plugging in given or arbitrary values of x.
The equation for 3y + 3y = -1 is 3y + 3y = -1.
-8x+3y=12 3y = 8x+12 y = (8/3)x + 4 So it will be a line with slope 8/3 and y intercept of 4
2x-11
(3,3)
3y + 4z + 12y = 3y -3y -3y ------------------------- 4z + 12y = 0 divide everything by 4 z + 3y = 0 -3y -3y z = -3y